The PEERS curriculum for school-based professionals : social skills training for adolescents with autism spectrum disorder - Laugeson, Elizabeth A. (New York ; London : Routledge ; Taylor & Francis, 2014)
The PEERS® Curriculum for School-Based Professionals brings UCLA's highly acclaimed and widely popular PEERS program into the school setting. This sixteen-week program, clinically proven to significantly improve social skills and social interactions among teens with autism spectrum disorder, is now customized for the needs of psychologists, counselors, speech pathologists, administrators, and teachers. The manual is broken down into clearly divided lesson plans, each of which have concrete rules and steps, corresponding homework assignments, plans for review, and unique, fun activities to ensure that teens are comfortable incorporating what they've learned. The curriculum also includes parent handouts, tips for preparing for each lesson, strategies for overcoming potential pitfalls, and the research underlying this transformative program.
1. Introduction and trading information -- 2. Two-way conversations -- 3. Electronic communication -- 4. Choosing appropriate friends -- 5. Appropriate use of humor -- 6. Starting and joining conversations -- 7. Exiting conversations -- 8. Good sportsmanship -- 9. Get-together -- 10. Handling arguments -- 11. Changing reputations -- 12. Handling teasing and embarrassing feedback -- 13. Handling physical bullying -- 14. Handling cyber bullying -- 15.Minimizing rumors and gossip -- 16.Final review, post-test assessment and graduation.
Includes bibliographical references and index.
Keywords: SOCIAL SKILLS -- STUDY AND TEACHING